Is one enough? Screen reader use among employed people who are blind or have low vision in the U.S. - McDonnall, Michele C.; Boydstun, Jamie; Steverson, Anne (Disability & Rehabilitation: Assistive Technology, 2025)
Screen reader software is a vital assistive technology (AT) that enables computer access for people who are blind or have low vision, but we know little about its use in the workplace. The purpose of this study was to learn about computer screen reader use among a group of legally blind workers, including type and number of screen readers used, factors associated with multiple screen reader use, and how multiple screen reader users select one for different tasks. Participants were 274 employed people in the U.S. who completed online or phone surveys and used screen readers on the job. Descriptive statistics, chi-square test, and logistic regression were used to analyze quantitative data, and content analysis was utilized with qualitative data. We found that JAWS was the predominant screen reader used, and most people utilized multiple screen readers. People who used multiple screen readers were less likely to report a challenge with working efficiently compared to sighted peers. Experiencing a problem while using a screen reader was the most common reason for deciding to use a different screen reader, followed by deciding based on knowledge that one screen reader works better than others for specific tasks. Several factors, in addition to having an AT or accessibility-related job, were associated with multiple screen reader use. Our findings suggest that using multiple screen readers can benefit workers in terms of efficiency and ability to troubleshoot problems experienced when using a screen reader, such as the inaccessibility or poor usability of digital content. IMPLICATIONS FOR REHABILITATION: Our findings clearly indicate that it is valuable for students, job seekers, and workers who are legally blind to have the ability to use more than one brand of screen reader. Rehabilitation professionals and assistive technology instructors should ensure that legally blind consumers learn how to utilize at least two different screen readers, with one or more that can serve as a back-up to their primary screen reader. Learning to problem-solve and troubleshoot screen reader problems is a valuable skill that assistive technology instructors should strive to teach students, along with embracing a continuous learning mindset related to assistive technology.